Characterization of human stem cell-derived hepatic stellate cells and liver sinusoidal endothelial cells during extended in vitro culture - Wilhelmsen, Ingrid; Amirola Martinez, Mikel; Stokowiec, Justyna; Wang, Chencheng; Aizenshtadt, Aleksandra; Krauss, Stefan (Frontiers in Bioengineering and Biotechnology, 2023)
Background: There is a significant need for predictive and stable in vitro human liver representations for disease modeling and drug testing. Hepatic stellate cells (HSCs) and liver sinusoid endothelial cells (LSECs) are important non-parenchymal cell components of the liver and are hence of relevance in a variety of disease models, including hepatic fibrosis.Pluripotent stem cell-(PSC-) derived HSCs (scHSCs) and LSECs (scLSECs) offer an attractive alternative to primary human material; yet, the suitability of scHSCs and scLSECs for extended in vitro modeling has not been characterized.In this study, we describe the phenotypic and functional development of scHSCs and scLSECs during 14 days of 2D in vitro culture. Cell-specific phenotypes were evaluated by cell morphology, immune fluorescence, and gene-and protein expression. Functionality was assessed in scHSCs by their capacity for intracellular storage of vitamin A and response to pro-fibrotic stimuli induced by TGF-β. scLSECs were evaluated by nitric oxide-and factor VIII secretion as well as endocytic uptake of bioparticles and acetylated low-density lipoprotein. Notch pathway inhibition and co-culturing scHSCs and scLSECs were separately tested as options for enhancing long-term stability and maturation of the cells.Both scHSCs and scLSECs exhibited a post-differentiation cell type-specific phenotype and functionality but deteriorated during extended culture with PSC line-dependent variability. Therefore, the choice of PSC line and experimental timeframe is crucial when designing in vitro platforms involving scHSCs and scLSECs. Notch inhibition modestly improved long-term monoculture in a cell line-dependent manner, while coculturing scHSCs and scLSECs provides a strategy to enhance phenotypic and functional stability.